Application of generalized aurora computed tomography to the EISCAT-3D project - Tanaka, Yoshimasa; Ogawa, Yasunobu; Kadokura, Akira; Aso, Takehiko; Gustavsson, Björn Johan; Brändström, Urban; Sergienko, Tima; Ueno, Genta; Saita, Satoko (Annales Geophysicae, 2024)
EISCAT_3D is a project to build a multi-site phased-array incoherent scatter radar system in northern Fenno-Scandinavia. We demonstrate via numerical simulation how useful monochromatic images taken by a multi-point imager network are for auroral research in the EISCAT_3D project. We apply the generalized aurora computed tomography (G-ACT) method to modelled observational data from real instruments, such as the Auroral Large Imaging System (ALIS) and the EISCAT_3D radar. G-ACT is a method for reconstructing the three-dimensional (3D) distribution of auroral emissions and ionospheric electron density (corresponding to the horizontal two-dimensional (2D) distribution of energy spectra of precipitating electrons) from multi-instrument data. It is assumed that the EISCAT_3D radar scans an area of 0.8° in geographic latitude and 3° in longitude at an altitude of 130 km with 10 × 10 beams from the radar core site at Skibotn (69.35° N, 20.37° E). Two neighboring discrete arcs are assumed to appear in the observation region of the EISCAT_3D radar. The reconstruction results from G-ACT are compared with those from the normal ACT as well as the ionospheric electron density from the radar. It is found that G-ACT can interpolate the ionospheric electron density at a much higher spatial resolution than that observed by the EISCAT_3D radar. Furthermore, the multiple arcs reconstructed by G-ACT are more precise than those by ACT. In particular, underestimation of the ionospheric electron density and precipitating electrons' energy fluxes inside the arcs is significantly improved by G-ACT including the EISCAT_3D data. Even when the ACT reconstruction is difficult due to the unsuitable locations of the imager sites relative to the discrete arcs and/or a small number of available images, G-ACT allows us to obtain better reconstruction results.